Pelatihan Penyusunan Laporan Keuangan Berbasis SAK-ETAP Bagi Pengurus Koperasi di Kabupaten Halmahera Utara - Eka Setiajatnika; Dady Nurpadi (E-Coops-Day, 2023)
The aim of the SAK-ETAP-based financial report preparation training for administrators in the North Halmahera Regency, North Maluku Province is so that administrators can improve their abilities in terms of recording and managing finances through financial reports. Most of the managers of cooperatives do not understand the proper way of recording financial reports, especially those related to cooperative accounting and its uses so cooperative managers need support from academics to receive training in preparing financial reports for cooperative managers. The method used in this community service is training and assistance in preparing cooperative financial reports through Tutorial and Discussion activities related to the problems of preparing and managing finances in each cooperative. The method of collecting data on community service activities is through observation and interviews with several cooperative administrators. The number of participants who took part in this training was 26 people who were cooperative administrators. The results of this training activity can be said to be successful, seen from the enthusiasm of the cooperative management during the training process and assistance in preparing cooperative financial reports based on SAK-ETAP